The Influence of Molarity Activity on the Green and Mechanical Properties of Geopolymer Concrete - Sarah Al-Qutaifi; Aliaa K. Hanan; Ahmed Jabbar Hamza (Construction Materials)
The usage of geopolymer-based materials (GPBMs) in concrete structures has been broadly promoted by the current construction sector. GPBMs have an outstanding influence on enhancing concrete mechanical properties. Geopolymers (GPs) also have a potential impact on reducing the carbon dioxide emissions emitted by the current cement production procedure. Therefore, this paper aims to evaluate the impact of some variables that affect green and mechanical properties of fly ash-based geopolymer concretes (FA–GPCs), i.e., different silica fume (SF) contents, alkaline activator solution (AAS) percentages, sodium silicate-to-sodium hydroxide (SS/SH) ratios, sodium hydroxide (NaOH) molarity, and additional water. A slump test was used to evaluate the concrete workability to assess the green properties of the designed fly ash-geopolymer concrete mixes (FA–GPCMs). The 14- and 28-day compressive strengths were used to evaluate the concrete’s mechanical properties. Results indicate that the workability of prepared FA–GPCMs reduced with improving SF content (5% to 30%), SS/SH ratio (1% to 3%), and NaOH molarity (10 M to 16 M), while reducing alkaline activator percentages to 35% resulted in a decrease in the FA–GPCMs’ workability. Also, increasing SF replacement percentages from 5% to 15% in FA–GPCMs resulted in significant 14- and 28-day FA–GP compressive strength enhancements compared to FA–GPCM produced with 0% SF, while SF contents of 20%, 25%, and 30% led to a decline in the 14- and 28-day FA–GPC compressive strength compared to that of G1–SF15%.